Religion, Myth and Ideology - Junginger, Horst (Method & theory in the study of religion, 2013)
The thirteen articles collected in Bruce Lincoln’s Gods and Demons, Priests and Scholars are a persuasive plea for an appropriate contextualization of religious phenomena in their mundane circumstances. Starting with the well-known Theses on Method that structure the book in methodological regard, each of the following texts is divided in a thorough historical research introduced or accompanied by extensive theoretical considerations. Particularly the case studies addressing problems of the Old Norse and Old Iranian history of religions are in-depth examinations of their own.Lincoln’s general interest is directed towards the analytical differentiation between the objects of the academic study of religion and their scholarly investigation. Only on the basis of a reflected distinction between both, the study of religion will achieve a deeper understanding of the attractiveness of religions and myths along with their capacity to adapt themselves to changing worldly conditions.